2023
DOI: 10.1177/08959048231153612
|View full text |Cite
|
Sign up to set email alerts
|

Different or Differentiated? Recoupling Policy and Practice in an Era of Accountability

Abstract: Differentiation is an instructional practice teachers employ to modify their classroom content, process, and products based on student readiness, interest, and learning profile. Many school districts recognize the benefits of differentiated instruction and thus mandate allotted classroom time for its implementation. In this article, we investigate how teachers in one such district resolved differentiation policy to practice in a high-stakes testing environment. We found, during the designated time for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Others stem from questions of cultural relevance among classroom populations, a lack of adherence to research-based practices, or continuing problems with teacher training. For instance, although teachers are familiar with scaffolding for students who need additional help, almost no differentiation happens “upward” for students who need additional challenge (Kenney et al, 2024). These are all issues thoroughly baked into the worldview that one classroom can meet all needs.…”
Section: The Problem With Problemsmentioning
confidence: 99%
“…Others stem from questions of cultural relevance among classroom populations, a lack of adherence to research-based practices, or continuing problems with teacher training. For instance, although teachers are familiar with scaffolding for students who need additional help, almost no differentiation happens “upward” for students who need additional challenge (Kenney et al, 2024). These are all issues thoroughly baked into the worldview that one classroom can meet all needs.…”
Section: The Problem With Problemsmentioning
confidence: 99%
“…Research shows that a typical fifth grade classroom might have a fiveto seven-grade academic achievement range (Peters et al, 2017;Rambo-Hernandez et al, 2020). We also know from research at the National Center for Research on Gifted Education that when teachers are given time to differentiate content and instruction, they tend to focus exclusively on struggling learners (Kenny et al, 2024).…”
mentioning
confidence: 99%
“…Broome (2020) noted pacing guides are currently a little-researched area of study and called for more research on effects of pacing guides on teacher autonomy. Our recent study on classroom differentiation (Kenney et al, 2023) revealed that teachers found district mandates for strict pacing guide adherence limited their enacted autonomy. Therefore, we probed this finding further in the current study by examining the reported perception and enactment of autonomy (e.g., Olivant, 2015; Parker, 2015; Sparks and Malkus, 2015) by elementary teachers in a diverse public school district in the southern United States.…”
mentioning
confidence: 99%